2022
DOI: 10.1186/s12870-022-03838-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis and molecular dissection of the SPL gene family in Fraxinus mandshurica

Abstract: Background SQUAMOSA promoter binding protein-like (SPL) is a unique family of transcription factors in plants, which is engaged in regulating plant growth and development, physiological and biochemical processes. Fraxinus mandshurica is an excellent timber species with a wide range of uses in northeastern China and enjoys a high reputation in the international market. SPL family analysis has been reported in some plants while SPL family analysis of Fraxinus mandshurica has not been reported. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The Zn-1 of SbSPL2 and the Zn-2 sequence of SbSPL4 were missing (Figure S2 ). Zn-1 of FmSPL9 and Zn-2 of FmSPL31/32 were also absent in Fraxinus mandshurica (He et al 2022a ). Domain changes or losses are not always negative and drive the expansion of gene families (Brand et al 2013 ; Wei et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Zn-1 of SbSPL2 and the Zn-2 sequence of SbSPL4 were missing (Figure S2 ). Zn-1 of FmSPL9 and Zn-2 of FmSPL31/32 were also absent in Fraxinus mandshurica (He et al 2022a ). Domain changes or losses are not always negative and drive the expansion of gene families (Brand et al 2013 ; Wei et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, some SPL genes in alfalfa ( Medicago sativa L.) are induced by drought, salt, and methyl jasmonate (Me JA) [ 49 ]. Several genes encoding SPL transcription factors demonstrated a notable increase in expression levels in Fraxinus mandshurica when exposed to ABA, cold, and salt treatments [ 50 ]. In addition, some AhSPL genes were also enriched for pathways acting in response to external stimulus (GO:0009605) ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have found significant expansion of the SPL gene in some dicots, such as Fraxinus mandshurica Rupr. [ 45 ] (36), Glycine max (Linn.) Merr.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of BpSPL s in apical buds and male inflorescences of Betula platyphylla is inversely proportional to the expression of miRNA156 , suggesting that BpSPL s may be involved in flower development [ 14 , 60 ]. Overexpression of FmSPL2 in transgenic Nicotiana tabacum L. resulted in taller plants, changes in the morphology and number of roots, rounded leaves, and an earlier flowering time [ 45 ]. In subfamily VII, VcSPL20 was significantly down-regulated during floral organ development in Vaccinium corymbosum L., while VcSPL35 was maintained at a high level [ 61 ].…”
Section: Discussionmentioning
confidence: 99%